2010
DOI: 10.1002/jsfa.3872
|View full text |Cite
|
Sign up to set email alerts
|

Production of trans‐free margarine stock by enzymatic interesterification of rice bran oil, palm stearin and coconut oil

Abstract: The interesterified fats showed desirable physical properties and suitable crystal form (beta' polymorph) for possible use as a spreadable margarine stock. Therefore, our result suggested that the interesterified fat without trans fatty acid could be used as an alternative to partially hydrogenated fat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 20 publications
2
50
0
Order By: Relevance
“…Elaidic acid is a characteristic trans FA which is generated by low quality catalysis during margarine production. Technologies have been developed to minimise trans FA production in industrial and cooking processes 198 , although they still appear in food consumed. Further advances in these technologies are required.…”
Section: Cardiovascular Health and Blood Lipidsmentioning
confidence: 99%
“…Elaidic acid is a characteristic trans FA which is generated by low quality catalysis during margarine production. Technologies have been developed to minimise trans FA production in industrial and cooking processes 198 , although they still appear in food consumed. Further advances in these technologies are required.…”
Section: Cardiovascular Health and Blood Lipidsmentioning
confidence: 99%
“…Medium-chain TAGs are hydrolyzed faster and more completely than long-chain TAGs 3 , hence, they are used immediately as energy sources in the body and avoid being stored in the adipose tissue 2 . Moreover, it has been shown that medium-chain TAGs may reduce the incorporation and storage of dietary fats and oil in adipose tissue 4 .…”
Section: Introductionmentioning
confidence: 99%
“…There have been a number of recent studies regarding EI of PS and RBO blends (8)(9)(10)(11)(12)(13), where PS was used as a source of saturated FAs that were transferred to the TAG structure of RBO in order to create low trans or trans-free fat blends with improved crystallization and melting characteristics for shortenings and margarines. However, in this study, PS was solvent-fractionated and only the solid hard palm stearin (hPS) fraction was used.…”
Section: Introductionmentioning
confidence: 99%